Reformulated Object Relations Theory: A Bridge Between Clinical Psychoanalysis, Psychotherapy Integration, and the Understanding and Treatment of Suicidal Depression - Shahar, Golan (Frontiers in Psychology, 2021)
Psychoanalysis has always felt comfortable conversing with the humanities (Freud, 1930; Jurist & Orfanos, 2016; Kohut, 1980), as well as with the more hermeneutic branches of social sciences (e.g., Freud, 1921; Paul, 1989; Powell, 2010). By the same token, psychoanalysis has always felt uncomfortable with empirical, quantitative science, whether medical or (neuro-)psychological (Blass & Carmeli, 2007; Bornstein, 2007; Leese, 2005). Like others in my own "tribe", I have repeatedly lamented this conflictual relationship between psychoanalysis and empirical science (e.g., Shahar, 2010, 2015a). In this article I seek to examine one of the most unfortunate, albeit poorly understood, consequences of the psychoanalysis-empirical science rift: The failure to pursue a dialogue with other schools of psychotherapy, primarily the cognitive-behavioral, manualized-interpersonal, emotion-focused, and family-systems perspective. I submit that this failure is unfortunate not only to our patients, who could benefit from an integrative perspective that preserves the wealth and wisdom of the psychoanalytic perspective while embracing the rigor of the aforementioned ones, but also to the development and growth of psychoanalysis itself, theoretical and clinical alike. In an attempt to defend this position, I focus primarily on a gnawing problem faced by clinicians from various disciplines and perspectives, i.e., suicidal depression.